2013
DOI: 10.1016/j.cub.2012.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Mask Is Required for the Activity of the Hippo Pathway Effector Yki/YAP

Abstract: Summary The Drosophila Yorkie (Yki) protein and its mammalian homolog Yes-associated protein (YAP) are potent growth promoters and YAP overexpression is associated with multiple types of cancer [1,2]. Yki and YAP are transcriptional co-activators and function as downstream effectors of the Hippo tumor suppressor pathway [1–4]. The regulation of Yki and YAP by the Hippo signaling pathway has been extensively investigated, however, how they regulate gene expression is poorly understood. To identify additional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 24 publications
7
90
0
1
Order By: Relevance
“…MASK is a cofactor of Drosophila Yorkie (Yki) and mammalian Yes-associated protein (YAP) in the Hippo signalling pathway, which controls tissue growth. The signalling function in this pathway is similar for Drosophila and human MASK (Sansores-Garcia et al, 2013;Sidor et al, 2013); however, MASK isoforms have not been found it human muscle. There is a sequence in the C. elegans genome that codes for a protein with homology to Drosophila, mouse and human MASK (Smith et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…MASK is a cofactor of Drosophila Yorkie (Yki) and mammalian Yes-associated protein (YAP) in the Hippo signalling pathway, which controls tissue growth. The signalling function in this pathway is similar for Drosophila and human MASK (Sansores-Garcia et al, 2013;Sidor et al, 2013); however, MASK isoforms have not been found it human muscle. There is a sequence in the C. elegans genome that codes for a protein with homology to Drosophila, mouse and human MASK (Smith et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…There are two smaller homologues of MASK in human cells: MASK1 (Ankhd1) and MASK2 (Ankrd17), which have the same domain structure as Drosophila MASK. The Drosophila protein (∼400 kDa) is larger than the human proteins (∼280 kDa), mainly due to a longer stretch of sequence between the ankyrin repeat domains (Sansores-Garcia et al, 2013;Sidor et al, 2013). MASK is a cofactor of Drosophila Yorkie (Yki) and mammalian Yes-associated protein (YAP) in the Hippo signalling pathway, which controls tissue growth.…”
Section: Discussionmentioning
confidence: 99%
“…It was later shown to regulate additional signalling cascades including the cancer-associated HIPPO (11)(12)(13)(14) and PINK/Parkin in Drosophila (15). Clinical epidemiological studies suggested that ANKHD1 is elevated and may be involved in acute leukaemia (16) and prostate cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, ANKHD1 associates with SHP2, however the biologic consequence of this protein interaction remains indeterminate (Traina, et al, 2006). ANKHD1 and YAP1 interaction has also been confirmed in human cells (HEK293 and DU145 cells) and modulates the Hippo signaling pathway activation, proliferation and cell cycle progression (Sidor, et al, 2013, Sansores-Garcia, et al, 2013, Machado-Neto, et al, 2014.…”
Section: Functionmentioning
confidence: 99%
“…In two independent cohorts of breast cancer patients, high expression of ANKHD1 was associated with worsened outcomes (Sansores-Garcia, et al, 2013).…”
Section: Prognosismentioning
confidence: 99%